(untitled) (Innovaciones Educativas, 2025)
The enrollment of children under the age of three in educational institutions has been increasing, presenting a series of challenges for families and early childhood educators. This manuscript systematizes the work carried out over the past decade at the Centro Infantil Laboratorio Ermelinda Mora (CILEM) to establish a respectful transition process for young children and to foster secure attachment within the educational environment. The analysis of the dissonances between theoretical frameworks and classroom practices began with a collaborative reading of core principles of early childhood development. Subsequently, classroom routines were recorded on video and analyzed collectively with educators to reflect on the alignment between guiding principles and actual practices. The manuscript highlights key theoretical foundations essential for working with children under the age of three and outlines the process of professional development and reflective practice undertaken by the staff. It also presents pedagogical and relational strategies that have proven effective in transforming institutional practices. The process of reflection and action enabled a deeper examination of everyday routines—often carried out automatically—uncovering underlying developmental goals and worldviews. The main outcome of this process was the creation of a shared institutional language, developed through interdisciplinary dialogue, and a more sensitive response to the needs of both families and young children, resulting in a positive impact on learning and development.